A Paleolimnological Investigation into the Ecological Impacts of Permafrost Thaw Slumping on Cladocerans (Branchiopoda, Crustacea) in the Mackenzie Delta Region (Northwest Territories, Canada) - Auger, Bradley Matthew (2021)
This thesis explores the ecological impacts of retrogressive thaw slumping on cladocerans (Branchiopoda, Crustacea) in Mackenzie Delta Region (Northwest Territories, Canada) lakes using paleolimnological techniques to answer the following questions: 1) Does thaw slumping increase UV exposure of Chydorus? 2) Are Daphnia absent in slump-affected lakes? I reconstructed UV exposure of Chydorus in a reference and slump-affected lake by measuring carapace absorbances at UV wavelengths. Carapace absorbances in the slump-affected lake were comparable to the reference lake, indicating Chydorus were not exposed to more UV radiation than in the reference lake. I also examined Daphnia ephippia in surface and pre-1850 sediments from 7 slump-affected and 7 unimpacted lakes, to confirm a 2017 zooplankton survey observation that Daphnia were absent in slump-affected lakes. Daphnia were not observed in slump-impacted lake sediments; however low sediment volumes likely underestimate Daphnia presence. My research provides new information on zooplankton biogeography in the Mackenzie Delta region.